Effect of Current Transformer Impedace on Secondary Injection Accuracy (Journal of University of Babylon for Engineering Sciences, 2018)
The traditional procedure of the secondary injection test includes splitting the secondary winding of current transformer from the test circuit. This work investigates whether the presence of the current transformer secondary winding inside the test circuit affects the accuracy of the test results or not. Matlab/Simulink has been used in this paper for modeling and simulating  the tested circuit. Paper results show that the accuracy of the test is not affected when the secondary winding of current transformer presence inside the test circuit.